Facilitating employees' and students' process towards nascent entrepreneurship. Issue 8 (9th November 2015) - Hietanen, Lenita
Abstract : Purpose: – The purpose of this paper is to investigate a model for facilitating employees' and full-time, non-business students' entrepreneurial capabilities during their optional entrepreneurship studies at one Finnish Open University. Design/methodology/approach: – The case study investigates the course in which transitions from employees or non-business students to nascent entrepreneurs are presupposed to happen. The examined phenomenon is the lecturer's (the author's) facilitating process. The key method is to support the ES students in developing their daily practices and reflecting on these from an entrepreneurial view. Findings: – For the ES students identified as latent nascent entrepreneurs, the development period facilitated by exploiting small-sized entrepreneurs' attributes, skills and behaviour mainly awakened intrapreneurship. Intrapreneurship was an unexpected phase because the lecturer did not offer it as an alternative. This necessitated the lecturer to investigate her instructions during the ES students' development processes to find out the crucial factors that might have awakened their intrapreneurship. Practical implications: – In the current case, intrapreneurship seems to be an essential phase between latent nascent and nascent entrepreneurship. Therefore, it is important to note the elements in the facilitation process that may strengthen intrapreneurship. The implications of latent nascent entrepreneurs' entrepreneurial processes should be further investigated, whether strengthening intrapreneurship would produce more nascent entrepreneurs than processes without noticing intrapreneurship. Originality/value: – Developing and reflecting on one's practices from an entrepreneurial viewpoint as an employee or a full-time, non-business student seem worthy of more examinations. Generally, opportunities for encouraging new start-ups by these people comprise an unknown area when considering supported entrepreneurial processes.